Removal of clarithromycin from aqueous solution using water/triton X-100/ ethanol/ olive oil green nanoemulsion method. (April 2021) - Mahdi, Wael A.; Hussain, Afzal; Bukhari, Sarah I; Alshehri, Sultan; Singh, Bhupinder; Ali, Naushad
Graphical abstract: Highlights: The contaminated water presents a serious threat to the aquatic and human health. Green nanoemulsion is a suitable approach to clean aqueous system. Rifampicin removal depended upon the water and olive oil contents. Abstract: The study aimed to develop a multicomponent water/Triton X-100/ethanol/olive oil (OLO) green nanoemulsion for adsorptive (liquid-liquid adsorption) removal of potential antimicrobial clarithromycin (CLA) from a bulk aqueous solution. Several nanoemulsions were fabricated using slow titration method followed by pseudo ternary phase diagram. Nanoemulsions (CNF1-CNF5) were selected based on thermodynamic stability, globular size, polydispersity index (PDI), viscosity and refractive index. Moreover, liquid- liquid adsorptive efficiency (removal efficiency as %RE) was carried out at varied time points (10, 20 and 30 min). Results showed that the concentration of oil (OLO) and water had remarkable impact on globular size, and viscosity of nanoemulsions. Moreover, percent removal efficiency of CLA from a bulk aqueous solution was influenced with the content of water, OA, globular size and viscosity of nanoemulsions. The formulation "CNF5″ comprised of 15%w/w of water, 48%w/w of Smix and 37%w/w of OLO was selected as an efficient green nanoemulsion to eliminate CLA from a bulk aqueous solution. The CNF5 had the lowest globular size (∼ 26.0 nm), minimum polydispersity index (0.119), optimum viscosity (94.2 cP), and the highest %RE of CLA. Transmission electron microscopy (TEM) result suggested that there was slight increment in nanoglobules which might be due to drug loading in lipid phase. The globular size of the exposed nanoemulsion with water containing CLA was relatively greater than unexposed nanoemulsion which can be correlated with TEM finding. The approach may be a suitable alternative to conventional method with obvious benefits such as simple, economic, rapid and scalable for large scale plant.